2021
DOI: 10.5851/kosfa.2020.e94
|View full text |Cite
|
Sign up to set email alerts
|

Taste-Active and Nutritional Components of Thai Native Chicken Meat: A Perspective of Consumer Satisfaction

Abstract: This research article was done by a group of scientists from 6 different departments and 4 universities. We have equally contributed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…At P1, the predominant free amino acid of both cooked CB and SH was glutamic acid. The findings were in agreement with previous studies addressing that glutamic acid was the predominant essential amino acid in raw broiler and spent hen meats, whereas the predominant non-essential amino acid was alanine [31]. Free amino acids have been involved in the characteristic tastes of food [32].…”
Section: Protein Digestibility Of Cooked Sh and Cb Breast Samples Dur...supporting
confidence: 92%
“…At P1, the predominant free amino acid of both cooked CB and SH was glutamic acid. The findings were in agreement with previous studies addressing that glutamic acid was the predominant essential amino acid in raw broiler and spent hen meats, whereas the predominant non-essential amino acid was alanine [31]. Free amino acids have been involved in the characteristic tastes of food [32].…”
Section: Protein Digestibility Of Cooked Sh and Cb Breast Samples Dur...supporting
confidence: 92%
“…In a previous comparison study between commercial broiler and Korean native chicken, the content of betaine in broiler muscle was reported significantly higher than in Korean native chicken (Jayasena, Jung, Bae, et al, 2015;Jayasena, Jung, Kim, et al, 2015). Similarly, Lengkidworraphiphat et al (2021) also reported that broiler breast muscle had a higher betaine content than other native chicken breeds in Thailand. In the present study, PM muscle of CBC had betaine content of approximately 4-, 3-, and 6-fold higher than AVC, HCB, and DSL, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, consistent with expectation, all four breeds fed with similar corn and soybean‐based commercial feeds were detected with myo‐inositol in chicken serum and PM muscle, respectively. Meanwhile, betaine is an alpha‐amino acid that naturally occurs in chickens, and plays an essential role in chicken metabolism (Jayasena, Jung, Bae, et al, 2015 ; Jayasena, Jung, Kim, et al, 2015 ; Lengkidworraphiphat et al, 2021 ; Saeed et al, 2017 ). In a previous comparison study between commercial broiler and Korean native chicken, the content of betaine in broiler muscle was reported significantly higher than in Korean native chicken (Jayasena, Jung, Bae, et al, 2015 ; Jayasena, Jung, Kim, et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the quantification and semi-quantification results showed that these amino acids’ content in VC was significantly higher than other chicken breeds. In previous studies, indigenous/native chickens of Thailand and Bali, Indonesia, were reported to have a high content of glutamic acid [ 38 , 39 ]. Moreover, slow-growing chicken breeds were also reported to have higher protein content and better amino acid profiles than fast-growing broilers [ 36 ].…”
Section: Discussionmentioning
confidence: 99%